1994
DOI: 10.1084/jem.180.5.1637
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii alters eicosanoid release by human mononuclear phagocytes: role of leukotrienes in interferon gamma-induced antitoxoplasma activity.

Abstract: SummaryToxoflasma gondii tachyzoites markedly alter the profile of eicosanoids released by human mononuclear phagocytes. Freshly isolated, 2-h adherent human monocytes release both cyclooxygenase (e.g., thromboxane [TX] B2, prostaglandin [PG] E2) and 5-1ipoxygenase (e.g., leukotriene [LT] ]]4, LTC4) products of arachidonic acid metabolism after stimulation by the calcium ionophore A23187 or ingestion of opsonized zymosan particles or heat-killed T. gondii. However, after incubation with viable T. gondii, norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 42 publications
2
35
0
6
Order By: Relevance
“…Wirth et al (11,12) reported that both LTB 4 and LTC 4 increased the phagocytosis and killing of Trypanosoma cruzi by peritoneal macrophages. The IFN-␥-mediated killing of Toxoplasma gondii by human monocytes was shown to be dependent on LT biosynthesis (13). In addition, Talvani et al (14) showed that during T. cruzi infection, LTB 4 is able to promote NO release and thereby kill this parasite.…”
mentioning
confidence: 99%
“…Wirth et al (11,12) reported that both LTB 4 and LTC 4 increased the phagocytosis and killing of Trypanosoma cruzi by peritoneal macrophages. The IFN-␥-mediated killing of Toxoplasma gondii by human monocytes was shown to be dependent on LT biosynthesis (13). In addition, Talvani et al (14) showed that during T. cruzi infection, LTB 4 is able to promote NO release and thereby kill this parasite.…”
mentioning
confidence: 99%
“…The cells degranulate and release LTB4, which damage tachyzoites [625] . Earlier study showed that LTB4-induced T. gondii cytotoxicity was characterized by vesiculation of the surface membrane and loss of the cytoplasmic contents of the organisms [624] , and the same cytotoxic changes were observed in tachyzoites after incubation with MCs [625] . Although the parasite inhibited mast cell degranulation by suppressing the mobilization of intracellular Ca 2+ mediated by C-phospholipase [630] , many biomediators, such as IL-6, can also be released from mast cells "selectively", without degranulation [631,632] .…”
Section: T Gondii Infectionmentioning
confidence: 84%
“…Effector cells against T. gondii include monocytes [617] , IFN-γ-activated macrophages [420,624] , neutrophils [623] , and platelets [417] . MCs also participate in host defense against the parasite .…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…Mice lacking cPLA 2 ␣ manifest a reduced clearance of bacteria in vivo (12), which is also the case for 5-lipoxygenase-deficient mice (5). It has been suggested that leukotrienes enhance microbicidal activity in macrophages by activating the NADPH oxidase (2,3,54). Thus, an argument has been made in favor of a therapeutic use of receptor agonists capable of activating cPLA 2 ␣ such as ATP in combination with other antimicrobial drugs to efficaciously treat complex infections (13,(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their demonstrated pro and antiinflammatory properties, phagocyte-derived eicosanoids have been implicated in the control of infections. In in vitro and in vivo models, the eicosanoids have been shown to modulate the microbicidal activity of phagocytes (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%